The metabolic pathway regulation in kidney injury and repair - Tang, Wenbin; Wei, Qingqing (Frontiers in Physiology, 2024)
Kidney injury and repair are accompanied by significant disruptions in metabolic pathways, leading to renal cell dysfunction and further contributing to the progression of renal pathology. This review outlines the complex involvement of various energy production pathways in glucose, lipid, amino acid, and ketone bodies metabolism within the kidney. We provide a comprehensive summary of the aberrant regulation of these metabolic pathways in kidney injury and repair. After acute kidney injury, there is notable mitochondrial damage and oxygen/nutrient deprivation, leading to reduced activity in glycolysis and mitochondrial bioenergetics. Additionally, disruptions occur in pentose phosphate pathway, amino acid metabolism, and the supply of ketone bodies. The subsequent kidney repair phase is characterized by a metabolic shift towards glycolysis, along with decreased fatty acid β-oxidation and continued disturbances in amino acid metabolism. Furthermore, the impact of metabolism dysfunction on renal cell injury, regeneration, and the development of renal fibrosis is analyzed. Finally, we discuss the potential therapeutic strategies by targeting renal metabolic regulation to ameliorate kidney injury and fibrosis and promote kidney repair.